Antiretroviral agents in pre-exposure prophylaxis: emerging and advanced trends in HIV prevention. (29th May 2019) - Yap, Pui Khee; Loo Xin, Griselda Lim; Tan, Yoke Ying; Chellian, Jestin; Gupta, Gaurav; Liew, Yun Khoon; Collet, Trudi; Dua, Kamal; Chellappan, Dinesh Kumar
Abstract: Objectives: Antiretroviral agents (ARVs) have been the most promising line of therapy in the management of human immunodeficiency virus (HIV) infections. Some of these ARVs are used in the pre-exposure prophylaxis (PrEP) to suppress the transmission of HIV. Prophylaxis is primarily used in uninfected people, before exposure, to effectively prevent HIV infection. Several studies have shown that ART PrEP prevents HIV acquisition from sexual, blood and mother-to-child transmissions. However, there are also several challenges and limitations to PrEP. This review focuses on the current antiretroviral therapies used in PrEP. Key findings: Among ARVs, the most common drugs employed from the class of entry inhibitors are maraviroc (MVC), which is a CCR5 receptor antagonist. Other entry inhibitors like emtricitabine (FTC) and tenofovir (TFV) are also used. Rilpivirine (RPV) and dapivirine (DPV) are the most common drugs employed from the Non-nucleoside reverse transcriptase inhibitor (NNRTIs) class, whereas, tenofovir disoproxil fumarate (TDF) is primarily used in the Nucleoside Reverse Transcriptase Inhibitor (NRTIs) class. Cabotegravir (CAB) is an analog of dolutegravir, and it is an integrase inhibitor. Some of these drugs are also used in combination with other drugs from the same class. Summary: Some of the most common pre-exposure prophylactic strategies employed currently are the use of inhibitors, namely entry inhibitors, non-nucleoside reverse transcriptase inhibitors, nucleoside reverse transcriptase inhibitors, integrase and protease inhibitors. In addition, we have also discussed on the adverse effects caused by ART in PrEP, pharmacoeconomics factors and the use of antiretroviral prophylaxis in serodiscordant couples.